1985
DOI: 10.1007/bf00915011
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes in the acquired immunodeficiency syndrome (AIDS): Relationship to disease manifestation, risk group, and immunologic defect

Abstract: Immune complex assays (and other immunologic tests) were performed on sera from 162 patients with the acquired immunodeficiency syndrome (AIDS) and 275 AIDS-related subjects. Immune complexes were detected in 89% of AIDS patients and 93% of homosexual men with lymphadenopathy. Immune complex levels in AIDS patients were not associated with a particular risk group or with types of opportunistic infection or malignancy; however, they correlated with other laboratory features of the immune defect (depression in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The presence of increased levels of ICs in association with primate lentivirus-induced disease is not a new finding. Early in the AIDS epidemic, high levels of ICs were detected in HIV-infected individuals, and after the virus was identified as the etiologic agent of AIDS, these ICs were shown to contain HIV virions or proteins (36,37,51,52,54). Consistent with SIV infection of macaques, the formation of HIV-ICs was related to high titers of HIV-specific antibodies, high levels of HIV virion RNA in plasma, and progressive disease (14,19,51,52,54).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The presence of increased levels of ICs in association with primate lentivirus-induced disease is not a new finding. Early in the AIDS epidemic, high levels of ICs were detected in HIV-infected individuals, and after the virus was identified as the etiologic agent of AIDS, these ICs were shown to contain HIV virions or proteins (36,37,51,52,54). Consistent with SIV infection of macaques, the formation of HIV-ICs was related to high titers of HIV-specific antibodies, high levels of HIV virion RNA in plasma, and progressive disease (14,19,51,52,54).…”
Section: Discussionmentioning
confidence: 60%
“…Early in the AIDS epidemic, high levels of ICs were detected in HIV-infected individuals, and after the virus was identified as the etiologic agent of AIDS, these ICs were shown to contain HIV virions or proteins (36,37,51,52,54). Consistent with SIV infection of macaques, the formation of HIV-ICs was related to high titers of HIV-specific antibodies, high levels of HIV virion RNA in plasma, and progressive disease (14,19,51,52,54). Furthermore, complement fixation by HIV-ICs was shown to facilitate dissemination of virus bound as an IC to B cells, dendritic cells, or erythrocytes, thus contributing directly to infection of CD4 ϩ T cells and to disease (32,36,37,53).…”
Section: Discussionmentioning
confidence: 99%
“…The cell-free virus half-life in plasma is less than 110 min, but the exact turnover mechanism(s) remains poorly understood (31). Several studies have shown that a portion of the cell-free virus exists as immune complexes (HIV IC) resulting from binding of specific antibody and/or complement deposition on the virion surface (7,22,24,36,37).…”
Section: Is An Important Route For Infection Of T Cells In Vivomentioning
confidence: 99%
“…During infection with human immunodeficiency virus type 1 (HIV-1), plasma virus can reach levels as high as millions of virus particles/milliliter (12,16), and a portion of this plasma virus is in the form of immune complexes (14,15,19,20). High levels of HIV are also found in lymphoid tissues, including lymph nodes (reviewed in references 3 and 8), and the total amount of virus found in this compartment within infected individuals has been estimated at 5 ϫ 10 10 virions (9).…”
mentioning
confidence: 99%